A comparative study between electrocautery and steel scalpel in making abdominal wall incision in caesarean section - Gupta, Sonika; Mehta, Anil; Gupta, Vikrant (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Electrocautery is commonly used in surgical practice. However, its use has been limited in skin due to the fear of tissue scarring, impaired wound healing and wound infection due to damaged tissue. To evaluate and compare the use of electrocautery and steel scalpel in making abdominal skin and deeper tissue incisions in caesarean section pfannenstiel incision with regard to operating time and postoperative wound complication rate. Methods: The study was a prospective randomized type conducted in the Department of Gynaecology, Government Hospital, Gandhi Nagar, Jammu. 120 patients undergoing caesarean section were divided into two groups, scalpel group in which skin and deeper tissue of abdominal wall were cut by scalpel and cautery group with electrocautery. Comparison was made between the two groups based on the above objectives. Results: In this study, we find that the operating time was less in electrocautery group and postoperative wound complications were comparable between two groups. Conclusions: The study demonstrates that electrocautery can be used as an alternative to steel scalpel for making abdominal skin incisions.